MELESTARIKAN TRADISI PENCAK SILAT BETAWI DI ERA DIGITAL - Romadlan, Said; Wahdiyati, Dini; Muhammad Maududi, Mukhlish; Kumari Putra, Gilang; Novita Sari, Ratih (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2025)
Pencak silat is one of Indonesia's original martial arts that has been recognized by the world. There are various pencak silat schools in Indonesia, one of which is Betawi’s pencak silat. The partner of this Community Partnership Program is a Betawi martial arts school, namely the H. Ridwan Pencak Silat Association in Condet, East Jakarta. Currently, the Betawi pencak silat school is facing obstacles, namely the lack of a systematic silat learning system, the lack of digital documentation of silat moves, and the limitations of participating in various pencak silat tournaments. Therefore, this Community Partnership Program offers a solution to solving these problems, namely the preparation of silat materials and teaching materials more systematically, developing a digital Betawi’s pencak silat learning model, and promoting Betawi’s pencak silat in various activities. For this reason, the methods of this activity include lectures and discussions in the form of workshops, the formulation of teaching materials through guided group discussions, and practices to document pencak silat moves in the form of videos. The results of this program are a deeper understanding the management of pencak silat associations, the preparation of Betawi’s pencak silat learning teaching materials more systematic, and the complete documentation of moves.